PEDAGOGICAL SEARCH IN THE CONTEXT OF METHODOLOGICAL COMPETENCE FORMATION - Vladimir A. Adolf (Высшее образование в России)
The author pays attention of the scientific and pedagogical community to one of the aspects of pedagogical search - the influence of results of scientific and pedagogical researches on the quality of pedagogical innovations in educational practice and the quality of training highly qualified teachers. The pedagogical search is considered as an integrated, interdisciplinary phenomenon of modern science. The author reveals the concept «methodological competence » of a teacher-researcher. The attention of the teacher-researcher focuses on the productive search of the evidence-based research.